2015
DOI: 10.1523/jneurosci.1090-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Modulations in Sensorimotor Postmovement and Foreperiod β-Band Activities Related to Error Salience Processing and Sensorimotor Adaptation

Abstract: In a recent study, Tan et al. (2014a,b) showed that the increase in ␤-power typically observed after a movement above sensorimotor regions (␤-rebound) is attenuated when movement-execution errors are induced by visual perturbations. Moreover, akin to sensorimotor adaptation, the effect depended on the context in which the errors are experienced. Thus the ␤-rebound attenuation might relate to neural processes involved in trial-to-trial adaptive mechanisms. In two EEG experiments with human participants, along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
123
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(139 citation statements)
references
References 64 publications
15
123
1
Order By: Relevance
“…According to this hypothesis, beta ERD would be associated to this sensorimotor adaptation when producing motor actions with incongruent visual and somatosensory feedback. This suggestion is consistent with a recent observation made by Torrecillos et al (2015). These authors found beta ERD during the preparation of a force-field adapted reaching movement, if the movement was preceded by a movement in the same force field (see also Thoroughman and Shadmehr, 2000).…”
Section: Sensorimotor Cortexsupporting
confidence: 92%
See 2 more Smart Citations
“…According to this hypothesis, beta ERD would be associated to this sensorimotor adaptation when producing motor actions with incongruent visual and somatosensory feedback. This suggestion is consistent with a recent observation made by Torrecillos et al (2015). These authors found beta ERD during the preparation of a force-field adapted reaching movement, if the movement was preceded by a movement in the same force field (see also Thoroughman and Shadmehr, 2000).…”
Section: Sensorimotor Cortexsupporting
confidence: 92%
“…These authors found beta ERD during the preparation of a force-field adapted reaching movement, if the movement was preceded by a movement in the same force field (see also Thoroughman and Shadmehr, 2000). Importantly, the use of movements with short duration in Torrecillos et al, (2015) study (i.e., 650 ms) may have favored the sensory remapping processes during movement planning rather than during movement execution. In the present experiment, participants were successively exposed to long periods with normal and incongruent feedback of similar durations (i.e.,~8 s).…”
Section: Sensorimotor Cortexmentioning
confidence: 95%
See 1 more Smart Citation
“…The main factor influencing frontal midline r Herrojo Ruiz et al r r 5162 r theta might be outcome probability, which is primarily associated with the non-phase-locked (induced) portion of theta oscillations [Hajihosseini and Holroyd, 2013]. Beta oscillations are crucial during sensorimotor learning and performance, as reflected in their involvement in processing self-produced pitch errors in piano performance [Herrojo Ruiz et al, 2011], or in sensorimotor adaptation [Tan et al, 2014;Torrecillos et al, 2015]. In addition, there is vast evidence linking changes in beta oscillations to the processing of different aspects of movements, such as movement-related cues, boundary elements of sensorimotor sequences or temporal intervals [Bartolo et al, 2014;Herrojo Ruiz et al, 2014a;Iversen et al, 2009;Leventhal et al, 2012;Oswal et al, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…For example, decreases of post event Beta have been associated with errors occurring during visual attention [11], or in the execution of movements [52]. In the former case, correct responses were associated with increased Beta synchrony in structures including bilateral parietal and frontal, as well as cingulate structures.…”
Section: Errors During Sustained Attention To Painmentioning
confidence: 99%